Post-Traumatic Osteoarthritis Assessment in Emerging and Advanced Pre-Clinical Meniscus Repair Strategies: A Review - Trivedi, Jay; Betensky, Daniel; Desai, Salomi; Jayasuriya, Chathuraka T. (Frontiers in Bioengineering and Biotechnology, 2021)
Surgical repair of meniscus injury is intended to help alleviate pain, prevent further exacerbation of the injury, restore normal knee function, and inhibit the accelerated development of post-traumatic osteoarthritis (PTOA). Meniscus injuries that are treated poorly or left untreated are reported to significantly increase the risk of PTOA in patients. Current surgical approaches for the treatment of meniscus injuries do not eliminate the risk of accelerated PTOA development. Through recent efforts by scientists to develop innovative and more effective meniscus repair strategies, the use of biologics, allografts, and scaffolds have come into the forefront in pre-clinical investigations. However, gauging the extent to which these (and other) approaches inhibit the development of PTOA in the knee joint is often overlooked, yet an important consideration for determining the overall efficacy of potential treatments. In this review, we catalog recent advancements in pre-clinical therapies for meniscus injuries and discuss the assessment methodologies that are used for gauging the success of these treatments based on their effect on PTOA severity. Methodologies include histopathological evaluation of cartilage, radiographic evaluation of the knee, analysis of knee function, and quantification of OA predictive biomarkers. Lastly, we analyze the prevalence of these methodologies using a systemic PubMed® search for original scientific journal articles published in the last 3-years. We indexed 37 meniscus repair/replacement studies conducted in live animal models. Overall, our findings show that approximately 75% of these studies have performed at least one assessment for PTOA following meniscus injury repair. Out of this, 84% studies have reported an improvement in PTOA resulting from treatment.